The meaning of advance directives in the lives of people with advanced long term conditions - Meron, Tikva (2014)
Background: Socio demographic and epidemiological change, together with the availability of medical technology, may prolong the process of dying. Antecedent control over end-of-life care (EoLC) may be sought by making an advance directive (AD). This option has been legalised in some countries including Israel, the setting of this study. In Israel, EoLC is set in the context of complex and interrelated religious and state regulations.